ZIF-derived in situ nitrogen decorated porous carbons for CO2 capture. Issue 9 (26th July 2016) - Pan, Ying; Xue, Ming; Chen, Mingyi; Fang, Qianrong; Zhu, Liangkui; Valtchev, Valentin; Qiu, Shilun
Abstract : A new group of N-doped hierarchical porous carbons with high surface areas, CO2 capacities and CO2 /N2 selectivity was prepared using a new mixed-ligand ZIF (JUC-160) as a precursor. The control of the size of JUC-160 crystals from nanometre and micron sizes allowed to study systematically the effect of the parent MOF's crystal size on the derived porous carbon materials. Abstract : Various N-doped hierarchical porous carbons were prepared by using a new mixed-ligand ZIF (zeolitic imidazolate framework) (JUC-160) as the precursor in a one-step synthetic route without any additional carbon sources or purification steps. The effect of the ZIF precursor crystal size on the textural properties of the derived porous carbons was systematically studied. Microporosity was dominant in micron-sized JUC-160 crystal derived porous carbons, while more mesopore volume was present in porous carbons obtained from nanometre-sized JUC-160 crystals. The mJUC160-900 sample, which had a high nitrogen content and micropore volume, exhibited the highest CO2 uptake, which is 5.50 and 3.50 mmol g −1 at 273 and 298 K, respectively. Moreover, the analysis based on the ideal adsorbed solution theory (IAST) exhibited a high adsorption selectivity for CO2 /N2 at 298 K and 1 bar ( S ads = 29).